THE STEPS (Dissertations the fruit growing troll) - Surányi, D. (International Journal of Horticultural Science, 2010)
The Steps (Dissertations the fruit growing troll) on front-page of volume are visible ruins and stairway of the famous Machu Picchu. Five  selfdetermined head stands the volume, essentially the author yet career one - one station, which the plant sexuality, the fruit cropping and sure environmental and plant health problems searching is comprising reached results engaged on 310 page, with 130 tables and 79 figures. The volume is brandnew notification shape in Hungarian and international scientific literature.